Beliefs and knowledge about post-traumatic stress disorder amongst resettled Afghan refugees in Australia. Issue 1 (December 2016) - Yaser, Anisa; Slewa-Younan, Shameran; Smith, Caroline; Olson, Rebecca; Guajardo, Maria; Mond, Jonathan
Abstract Background Resettled refugees are at high risk of trauma-related mental health problems, yet there is low uptake of mental health care in this population. Evidence suggests poor 'mental health literacy' (MHL) may be a major factor influencing help-seeking behaviour among individuals with mental health problems. This study sought to examine the MHL of resettled Afghan refugees in Adelaide, South Australia. Methods Interviews were completed with 150 (74 males; mean age 32.8 years, SD = 12.2) resettled Afghan refugees living in Adelaide, South Australia. A convenience sampling method was employed and participants were comprised of volunteers from the Afghan community residing in the northern suburbs of Adelaide. Following informed consent participants were presented a culturally appropriate vignette describing a fictional person suffering from posttraumatic stress disorder (PTSD). This was followed by a series of questions addressing participants' knowledge and understanding of the nature and treatment of the problem described. Self-report measures of PTSD symptoms and co-morbid psychopathology were also administered. Results Thirty-one per cent of the respondents identified the problem depicted in the vignette as being PTSD, while 26 per cent believed that the main problem was 'fear'. Eighteen per cent of participants believed that 'getting out and about more/finding some new hobbies' would be the most helpful form of treatment for the problem described, followed by 'improving their diet' and 'getting more exercise' (16 %). Conclusion The results of this study demonstrate aspects of MHL that appear to be specific to Afghan refugees who have resettled in Australia. They indicate the need for health promotion and early intervention programs, and mental health services, to recognise that variation in MHL may be a function of both the cultural origin of a refugee population and their resettlement country. Such recognition is needed in order to bridge the gap between Western, biomedical models for mental health care and the knowledge and beliefs of resettled refugee populations.